Oxidative capacity and hemolytic activity of settled dust from moisture‐damaged schools. (21st January 2019) - Huttunen, Kati; Wlodarczyk, Anna J.; Tirkkonen, Jenni; Mikkonen, Santtu; Täubel, Martin; Krop, Esmeralda; Jacobs, José; Pekkanen, Juha; Heederik, Dick; Zock, Jan‐Paul; Hyvärinen, Anne; Hirvonen, Maija‐Riitta; et al.
Abstract: Exposure to moisture‐damaged indoor environments is associated with adverse respiratory health effects, but responsible factors remain unidentified. In order to explore possible mechanisms behind these effects, the oxidative capacity and hemolytic activity of settled dust samples (n = 25) collected from moisture‐damaged and non‐damaged schools in Spain, the Netherlands, and Finland were evaluated and matched against the microbial content of the sample. Oxidative capacity was determined with plasmid scission assay and hemolytic activity by assessing the damage to isolated human red blood cells. The microbial content of the samples was measured with quantitative PCR assays for selected microbial groups and by analyzing the cell wall markers ergosterol, muramic acid, endotoxins, and glucans. The moisture observations in the schools were associated with some of the microbial components in the dust, and microbial determinants grouped together increased the oxidative capacity. Oxidative capacity was also affected by particle concentration and country of origin. Two out of 14 studied dust samples from moisture‐damaged schools demonstrated some hemolytic activity. The results indicate that the microbial component connected with moisture damage is associated with increased oxidative stress and that hemolysis should be studied further as one possible mechanism contributing to the adverse health effects of moisture‐damaged buildings.